2020
DOI: 10.1159/000505607
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bone Conduction Stimulation Applied Directly to the Otic Capsule Measured at Promontory: Assessment in Cadavers

Abstract: Introduction: The aims of this study included: (a) to develop a method of direct acoustic bone conduction (BC) stimulation applied directly to the otic capsule, (b) to investigate the effect of different stimulation sites on the promontory displacement amplitude, and (c) to find the best stimulation site (among 2 located directly on the otic capsule and 1 standard site approved for clinical use) that provides the greatest transmission of vibratory energy. Methods: Measurements were performed on 9 cadaveric who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The results of the mentioned studies [Kwacz et al, 2019;Lachowska et al, 2019;Niemczyk et al, 2020] present a potential of new stimulation sites that could be introduced in the field of BC hearing rehabilitation. However, both new BC stimulations sites involved drilling the bone near the SC, which might be questionable in terms of the safety of this procedure.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The results of the mentioned studies [Kwacz et al, 2019;Lachowska et al, 2019;Niemczyk et al, 2020] present a potential of new stimulation sites that could be introduced in the field of BC hearing rehabilitation. However, both new BC stimulations sites involved drilling the bone near the SC, which might be questionable in terms of the safety of this procedure.…”
Section: Discussionmentioning
confidence: 98%
“…The distance plays an important role, and the shorter the distance is the more efficient the stimulation is [Stenfelt et al, 2000;Stenfelt and Goode, 2005;Eeg-Olofsson et al, 2008, 2013Kwacz et al, 2019;Lachowska et al, 2019;Niemczyk et al, 2020]. Kwacz et al [2019], Niemczyk et al [2020], and Lachowska et al [2019] demonstrated that BC vibrations applied directly to the otic capsule seem to be more efficient than if applied outside the petrous part of the temporal bone. The authors sought to investigate the potential benefits of the proposed alternative stimulation sites, comparing them to the standard BC implants with stimulation applied to the squamosal portion of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments on dry human temporal bones and skulls showed that acceleration components of the OC vibrations measured during BC stimulation depended on the distance from the stimulation site to the inner ear 12 and the implant location 13 . Studies on cadaveric human heads 14 and patients 15 showed that the results for stimulation on the OC site were several times as good as for implantation on the temporal bone squamous.…”
Section: Introductionmentioning
confidence: 97%